2014
DOI: 10.5604/20831862.1125286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat exposure in the absence of hyperthermia on power output during repeated cycling sprints

Abstract: The aim of this study was to investigate the effects of heat exposure in the absence of hyperthermia on power output during repeated cycling sprints. Seven males performed four 10-s cycling sprints interspersed by 30 s of active recovery on a cycle ergometer in hot-dry and thermoneutral environments. Changes in rectal temperature were similar under the two ambient conditions. The mean 2-s power output over the 1st–4th sprints was significantly lower under the hot-dry condition than under the thermoneutral cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…For example, there was a clear difference in peak power output between INSP (1097 ± 148 W) and MATCH (773 ± 122 W) exercise conditions. In a typical sprint, power output peeks within 1-2 s and progressively declines as the sprint continues (23, 45). When sprints are repeated and separated by incomplete recovery periods, both peak and mean power output gradually decline as fatigue accumulates (14, 44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there was a clear difference in peak power output between INSP (1097 ± 148 W) and MATCH (773 ± 122 W) exercise conditions. In a typical sprint, power output peeks within 1-2 s and progressively declines as the sprint continues (23, 45). When sprints are repeated and separated by incomplete recovery periods, both peak and mean power output gradually decline as fatigue accumulates (14, 44).…”
Section: Discussionmentioning
confidence: 99%
“…After a 7-min warm-up consisting of 5 min of unloaded cycling at 60-70 rpm and two 4 s sprints (separated by 1 min), subjects rested for another 2.5 min before the repeated-sprint protocol was initiated. The repeated-sprint protocol was ten consecutive 10 s sprints separated by 30 s passive rest (4, 2123). Subjects were instructed to give an “all-out” effort for every sprint and verbally encouraged throughout to promote a maximal effort.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence of group III/IV muscle afferents reflexively regulating CMO and exercise performance was shown in studies on humans in which 31 P magnetic resonance spectroscopy and muscle afferent block were used 5,15) . In the magnetic resonance spectroscopy study, when the muscle force throughout 5 min of all-out maximal isometric contractions (60 MVCs) converged to 54% MVC, muscle metabolic milieu associated with peripheral fatigue at the end of the all-out contractions was similar to that at task failure of submaximal isometric contraction with 54% MVC 5) .…”
Section: Viewpoint 1: Muscle Afferent Feedback From Active Limb Musclmentioning
confidence: 99%
“…Additionally, Matsuura et al 31) have suggested that changes in cognitive process by heat exposure alter power profiles, but not peak and mean power output, during each cycling sprint in RCS. Therefore, we also must carefully analyze muscle force and power during exercise and take into account the contractile regimen applied to elucidate the interplay between psychological factors and group III/IV muscle afferent feedback.…”
Section: Perspective For Further Researchmentioning
confidence: 99%
“…For instance, a 24 s recovery has been used in protocols of 5 × 6 s (number of trials × duration of each trial) [16]; a 20 and 90 s recovery has been used in 12 × 4 s [18]; a 25, 50 and 100 s recovery in 10 × 5 s [24]; a 30 s recovery in 4 × 10 s [21], 5 × 6 s [9] and 6×6 s protocols [8]; 30 s, 1 and 5 min recovery in 10 × 10 s [27]; and a 40 s recovery in a 10×10 s protocol [17]. Moreover, longer recovery times have ranged from 1.5, 3 and 6 min in 2 × 30 s [3]; 3 min in 10 × 10 s [25]; 4 min in 3 × 30 s [32] and in 6 × 30 s protocols [20]; 5 min in 5 × 60 s [7]; and 20 min in a 3 × 30 s protocol [1].…”
Section: Introductionmentioning
confidence: 99%